The Length Of Surgery Is Associated With The Occurrence Of Shivering In Patients Who Have Undergone Spinal Block Anesthesia After Surgery At Masyithoh Bangil Hospital - Prawito, Prawito; Zatihulwani, ELiza Zihni; Sholikhah, Dwi Uswatun (Universitas Tribhuwana Tunggadewi, 2025)
Shivering is a problem that often occurs in patients undergoing surgery due to spinal block anesthesia or general anesthesia After spinal anesthesia, shivering is common during the intraoperative phase until the postoperative recovery phase. This study aims to analyze the relationship between the duration of surgery and the incidence of shivering in postoperative patients using spinal block anesthesia technique at RSI Masyithoh Bangil. The sampling method in this study used the accidental sampling technique involving 62 respondents. The instrument used was a patient observation form that recorded the duration of surgery and the occurrence of shivering. The results of the Spearman rho test showed a relationship between the duration of surgery and the incidence of shivering in patients using the spinal block anesthesia technique, with a p-value of 0.000 (p0.05) and a value of r=0.872. Based on these findings, it can be concluded that there is a very strong relationship between the duration of surgery and the occurrence of shivering in postoperative patients using the spinal anesthesia technique at RSI Masyithoh Bangil